Some functional properties of the matrix game value - Vilkas, E. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Э. Вилкас. Некоторые функциональные свойства значения матричной игрыE. Vilkas. Funkcionalinės lygties su lošimo reikšmės operatoriumi sprendimo klausimu